Antibody-induced crosslinking and cholesterol-sensitive, anomalous diffusion of nicotinic acetylcholine receptors - Mosqueira, Alejo (2020)
Fil: Mosqueira, Alejo. Pontificia Universidad Católica Argentina. Facultad de Ciencias Médicas. Instituto de Investigaciones Biomédicas. Laboratorio de Neurobiología Molecular; Argentina